2006
DOI: 10.1177/1074248406288757
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pyrroloquinoline Quinone and/or Metoprolol on Myocardial Infarct Size and Mitochondrial Damage in a Rat Model of Ischemia/Reperfusion Injury

Abstract: The cardioprotective effectiveness of low-dose pyrroloquinoline quinone (PQQ, 3 mg/kg) was compared with metoprolol, a beta(1)-selective adrenoceptor antagonist. Rats underwent 30 minutes of left anterior descending coronary artery occlusion and 2 hours of reperfusion. Metoprolol and/or PQQ were given at the onset of reperfusion to mimic clinical treatment. Metoprolol and/or PQQ reduced infarct size and protected against ischemia-induced left ventricular dysfunction after 2 hours of reperfusion. Combined thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 48 publications
1
59
0
5
Order By: Relevance
“…It has been reported that PQQ can stimulate the activation of cAMP response elementbinding protein (CREB) in combination with some transcription factors such as Nrf1, Nrf2 and mitochondrial transcription factors, enhancing mitochondriogenesis Stites et al, 2006;Zhu et al, 2006;Chowanadisai et al, 2010), whereas the Nrf2/ARE signaling pathway has been recognized as a key contributor to the cellular response to neuronal injury in vitro and in vivo (Shih et al, 2005). In this study, we measured the expression level of Nrf2 and some related transcript factors to demonstrate whether Nrf2/ARE signaling was influenced by PQQ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PQQ can stimulate the activation of cAMP response elementbinding protein (CREB) in combination with some transcription factors such as Nrf1, Nrf2 and mitochondrial transcription factors, enhancing mitochondriogenesis Stites et al, 2006;Zhu et al, 2006;Chowanadisai et al, 2010), whereas the Nrf2/ARE signaling pathway has been recognized as a key contributor to the cellular response to neuronal injury in vitro and in vivo (Shih et al, 2005). In this study, we measured the expression level of Nrf2 and some related transcript factors to demonstrate whether Nrf2/ARE signaling was influenced by PQQ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…41 Furthermore, Zhu et al have showed that in a rat model ischemia/reperfusion injury, metoprolol produced cardioprotection via hemodynamic effects. 42 More recently, Omerovic et al suggest that metoprolol attenuates post-infarct structural remodeling, without concomitant improvement in myocardial energy metabolism and function in rats with chronic congestive heart failure, 43 but authors could not completely explain which effect is responsible from this improvement.…”
Section: Discussionmentioning
confidence: 99%
“…PQQ was earlier known to regulate different abnormalities, 11,51 which are indirectly associated with diabetic complications. Now our findings ascertain that PQQ has also the potential to regulate STZ-induced damage to cardiac tissues.…”
Section: Effects Of Pyrroloquinoline Quinone and Vitamin C On Diabetementioning
confidence: 99%
“…After rendering DM/ hyperglycemia, animals of group IV, V and VI were treated i.p. with three different doses of PQQ (5, 10 and 20mg/kg/day, respectively for 15 days); 11,15 group VII animals received Vit.C (50mg/kg/day (i.p. ), for 15 days).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation